Optimization of effective parameters on solar updraft tower to achieve potential maximum power output: A sensitivity analysis and numerical simulation - Milani Shirvan, Kamel; Mirzakhanlari, Soroush; Mamourian, Mojtaba; Kalogirou, Soteris A. (My University, 2017)
In this paper, an axisymmetric 2-D numerical simulation and sensitivity analysis are carried out to obtain the potential maximum power output in a solar updraft tower power plant. The geometrical dimensions of the physical model of the studied solar updraft tower are based on the prototype installed at Manzanares. The sensitivity analysis is performed by utilizing the Response Surface Methodology. The effects of various parameters on the maximum potential power output of the solar updraft tower power plant are investigated and include the entrance gap of collector (2 m ≤ CG ≤ 6 m), tower diameter (5 m ≤ DT ≤ 10 m), tower height (200 m ≤ HT ≤ 220 m) and collector roof inclination (0° ≤ θ ≤ 5°). It is found that the potential maximum power output enhances with the tower diameter and height, and reduces as the entrance gap of collector is increased. Additionally, the sensitivity analysis revealed that the sensitivity of the potential maximum power output to (CG), reduces as (CG), (DT) and (θ) are increased. Moreover, its sensitivity to (DT) reduces as (DT), (θ) and (HT) are increased but increases with (CG). It is also found that to maximize the potential maximum power output, the effective parameters must have the values of CG = 2 m, DT = 10 m, HT = 220 m and θ = 0°.
Keywords: Numerical simulation; Power output; Response surface methodology; Sensitivity analysis; Solar updraft tower